Russian and European Tendencies in the Work of Ivan Zubov, Russian Engraver of the Early 18th century - Vasilyeva, Alexandra M. (Actual Problems of Theory and History of Art, 2025)
The article concerns with the problem of different influences on Russian printmaking of the early 18th c. in the works by Russian engraver Ivan Zubov, whose artistic personality was formed by the old Russian art tradition (icon painting) and by European printmaking experience (Dutch etchings).
Keywords: Russian printmaking; Petrine time; tradition; interaction; Ivan Zubov